Tinjauan Kimia Medisinal Senyawa Fenol dari Ekstrak Daun dan Biji Pepaya (Carica papaya) sebagai Anti Kanker - Devi Wulandari; Saeful Amin; Nida Atsila Anamareri; Atiqoh Azizah (Lembaga Pengembangan Kinerja Dosen, 2025)
Purpose: The aim of this study is to measure the total phenolic content in papaya (Carica papaya L.) leaf and seed extracts and to evaluate their potential as anticancer agents based on their antioxidant activity. Methodology/approach: Location & Materials: Papaya leaves and seeds were sourced from Manoko, Bandung. Extraction: The samples were washed, dried at 45°C, powdered, and extracted with 70% ethanol using the reflux method. Analysis: Total phenolic content was measured using a UV-Vis spectrophotometer at 761 nm after reacting extracts with Folin-Ciocalteu reagent and sodium carbonate. Results were compared to a gallic acid standard curve. Supporting Methods: Literature review on medicinal chemistry and anticancer drug development, as well as qualitative analysis using thin-layer chromatography (TLC) for main phenolic compounds. Results/findings: Papaya leaf and seed extracts contain significant phenolic compounds, including flavonoids and phenolic acids. These phenolics contribute to antioxidant activity, which helps protect cells from oxidative damage linked to cancer. Previous studies show papaya leaf extract can act as an immunomodulator and anticancer agent, while papaya seed contains benzyl isothiocyanate, which inhibits cancer cell growth. Limitations: The study only measures total phenolic content and does not isolate or identify individual active compounds. Anticancer activity is inferred from phenolic content and literature, not directly tested in vivo or in clinical trials. Contribution: This research provides scientific evidence that papaya leaves and seeds are promising natural sources of phenolic compounds with antioxidant and potential anticancer properties. The findings support further research in pharmacy, medicinal chemistry, and oncology, especially for developing plant-based anticancer agents.